Hospital pharmacists’ mental health during home isolation in the post-pandemic era of COVID-19: influencing factors, coping strategies, and the mediating effect of resilience - Yin, Zhao; Wang, XiangYu; Lu, Xiaojing; Fu, Hang (Frontiers in Public Health, 2024)
There is a notable research gap on the mental health challenges faced by hospital pharmacists in the post-pandemic era. Therefore, the present study aims to explore mental health status, influencing factors, coping strategies, and the mediating effect of resilience of home quarantine hospital pharmacists (HQHPs).: An embedded mixed-method study was conducted in Zhengzhou, a megalopolis in central China, from 20 October to 3 November 2022. For the qualitative study, semi-structured interviews and focus group discussions were conducted among HQHPs to understand their mental health state，the factors that affect their mental health, and the alleviating strategies they used. For the quantitative study, the Generalized Anxiety Disorder Scale (GAD-7) and the Chinese version of the Connor-Davidson Resilience Scale (CD-RISC-25) were used to explore the mental health level of HQHPs. Meanwhile, the mediating effect of resilience was explored and verified with the bootstrap method or the structural equation model. Results: 20 HQHPs participated in the qualitative study. Two themes were identified in terms of the factors that influenced the HQHPs' mental health levels. The positive factors include optimism, family company, and connection with friends, while the negative factors include inadequate supplies, inadequate information, and other emergencies. 210 HQHPs participated in the quantitative study, with a median resilience score of 66 [55.75, 74] in the lowest score range and an anxiety score of 5 [2, 7] in the mild anxiety range. The correlation analysis showed that nine of the ten influencing factors identified in qualitative research were positively correlated with CD-RISC-25 scores and negatively correlated with the GAD-7 score. The mediating effect of resilience on anxiety was significant (95% bootstrap CI [-1.818, -0.384], p＜ 0.001; or 95% bootstrap CI [-1.174, -0.430], p＜0.001). Conclusion: Even in the post-epidemic era, hospital pharmacists face psychological challenges. They actively address these issues based on accumulated experience and a stabilized mindset. In this process, resilience plays a significant mediating role.